Democratic Parenting Styles in Developing the Moral Intelligence of Children Aged 5–6 Years in Gemuhan Asa Village - Maria Apriani; Dwi Nugroho Hidayanto; Febry Maghfirah (Jurnal CARE (Children Advisory Research and Education), 2026)
Fostering independence through appropriate parenting styles is essential for a child's development. Independence needs to be cultivated to support a child's physical, emotional, social, financial, and intellectual growth from infancy through adulthood. This study aimed to examine the parenting styles employed by parents and the obstacles faced in developing the moral intelligence of children aged 5–6 years. A descriptive qualitative approach was used. The study subjects consisted of one parent and one child. Data collection methods included observation, interviews, and documentation. Data analysis followed the Miles and Huberman (2014) framework, comprising four stages: data collection, data reduction, data display, and conclusion drawing. The study, conducted in Gemuhan Asa Village, revealed that (1) the parenting style used to develop the child's moral intelligence involved monitoring the child's behavior to ensure it remained aligned with positive conduct, as well as engaging the child in discussions before the parents made decisions regarding activities or rules. Obstacles faced by the parents in instilling moral intelligence included the child's difficulty in heeding advice when in crowded environments, the child's tendency to become emotional when struggling with a task, and the influence of the environment when the child played outdoors. These findings demonstrate that a democratic parenting style is effective in helping to develop a child's moral intelligence.